The Development of Badminton Skills Test Instruments for Athletes in Age of Children, Cub, Teenager and Youth - Williyanto, Septian; Nasuka, Nasuka; Yudha Kusuma, Donny Wira (Journal of Physical Education and Sports, 2018)
The study aims to produced development of Badminton Skills Test Instrumens for athletes in age groups of children, cub, teenager and youth. This study is a type of Research and Development (R & D). In this study, the steps which should be done are: (1) preliminary study, (2) planning (analysis), (3) initial draft design, (4) draft validation, (5) small-scale product test and revision, (6) big-scale product test and revision, (7) result. The product produced in this study are badminton skill test instrumens, there are: (1) short-serve, (2) long-serve, (3) forehand lob, (4) forehand smash, (5) forehand drop shot, and (6) footwork for athletes in age children, beginners, teenagers and cadets which can be equipped with the test norms. The result of validations from the expert of academic, trainers and practitioners (player) of badminton as a whole stated that ‘very good’ with average score 3,66. Conclusion in this study is that based on the result of the data and expert’s judgments, the development of badminton skill test instrumen product for children, beginners, teenagers and cadets are worthy of being used as a standard badminton test instrumens. The suggestion from the researcher is that the result of this development can be used as one of alternative test for the basic skills assessment technique of local badminton athletes.